Sensemaking, sensegiving and absorptive capacity in complex procurements - Prior, Daniel D.; Keränen, Joona; Koskela, Sami (Elsevier, 2018)
This study explores and describes i) the nature of knowledge exchange processes at the frontline employee (FLE) level and ii) how FLE sensemaking processes affect buyer firm knowledge management practices in complex procurement contexts. The study utilizes an in-depth case analysis in the mining industry to identify a taxonomy of four buyer sensemaking investment/supplier collaboration profiles, to describe three sensegiving supplier roles (“confidence builders”, “competent collaborators”, and “problem-solvers”) and to explore how these evolve during complex procurement implementation. The study concludes with a conceptual model of the apparent linkages between sensemaking, sensegiving and buyer firm absorptive capacity in complex procurements. This study shows how micro-level (FLE) interactions influence macro-level knowledge integration (absorptive capacity) in the buyer firm. For managers, the study shows how the allocation of time and resources affects FLE-level knowledge exchange, with ultimate effect on buyer firm absorptive capacity.
Keywords: B2B; knowledge management; Solutions; Knowledge intensive business; Case study; Supplier relationships